Association Between Admission Pulse Pressure and Long-Term Mortality in Elderly Patients With Type 2 Diabetes Mellitus Admitted for Acute Coronary Syndrome: An Observational Cohort Study - Wang, Zijian; Li, Xiaoran; Wang, Yichun; Bao, Boyi; Ding, Xiaosong; Li, Hongwei; Li, Weiping (Frontiers in Cardiovascular Medicine, 2022)
Objective: To assess the effect of pulse pressure (PP) at admission on long-term cardiac and all-cause mortality among elderly patients with type 2 diabetes mellitus (T2DM) admitted for acute coronary syndrome (ACS). Methods: This is a retrospective observational study. The patients aged at least 65 years with T2DM and ACS from January 2013 to April 2018 were enrolled, and divided into 4 groups according to admission PP: <50 mmHg; 50-59 mmHg; 60-69 mmHg and ≥70 mmHg. Multivariate Cox proportional hazards regression analyses and restricted cubic spline were performed to determine association between PP and outcomes (cardiac and all-cause death). Results: A total of 2587 consecutive patients were included in this cohort study. Mean follow-up time was 39.2 months. The incidences of cardiac death and all-cause death were 6.8% (n=176) and 10.8% (n=280), respectively. After multivariate adjustment in whole cohort, cardiac and all-cause mortality were significantly higher in PP <50 mmHg group and PP ≥70 mmHg group, compared with PP 50-59 mmHg group. Further analysis in acute myocardial infarction (AMI) subgroup confirmed PP <50 mmHg was associated with cardiac death [hazard ratios (HR) 2.92, 95% confidence interval(CI) 1.45-5.76, P=0.002] and all-cause death (HR 2.08, 95% CI 1.20-3.58, P=0.009). Meanwhile, PP ≥70 mmHg was associated with all-cause death (HR 1.78, 95% CI 1.05-3.00, P=0.031). However, admission PP did not appear to be a significantly independent predictor in unstable angina pectoris (UAP) subgroup. There is a U-shaped correlation between PP and cardiac and all-cause mortality in whole cohort and UAP subgroup, and J-shaped correlation in AMI subgroup, both with a nadir at 50-59 mmHg. Conclusions: In elderly patients with T2DM admitted for ACS, admission PP is an independent and strong predictor for long-term cardiac and all-cause mortality, especially in AMI patients.